2020
DOI: 10.1021/acsomega.9b03049
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel and Hydrogen Production in a Combined Palm and Jatropha Biomass Biorefinery: Simulation, Techno-Economic, and Environmental Evaluation

Abstract: The biodiesel from lignocellulosic materials has been widely recognized as an alternative fuel to meet energy requirements worldwide, facing fossil fuel depletion, and emerging energy policies. In this work, the biorefinery approach was applied for biodiesel production from jatropha and palm oils in order to make it economically competitive by the utilization of residual biomass as the feedstock for obtaining hydrogen via steam reforming of glycerol and gasification. The linear chains for hydrogen and diesel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 67 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Comparing with the economic results for other biorefineries it was found that the return on investment for a lignocellulosic multi feedstock biorefinery was 32% [ 24 ], and for a combined palm and jatropha biomass biorefinery for biodiesel and hydrogen production was 33.18% [ 41 ], which shows that the mass integrated approach for shrimp biorefinery is more economically attractive. The net profits for the biorefinery were estimated to be up to 95% higher than the net profit obtained in the chitosan production process from shrimp exoskeleton [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparing with the economic results for other biorefineries it was found that the return on investment for a lignocellulosic multi feedstock biorefinery was 32% [ 24 ], and for a combined palm and jatropha biomass biorefinery for biodiesel and hydrogen production was 33.18% [ 41 ], which shows that the mass integrated approach for shrimp biorefinery is more economically attractive. The net profits for the biorefinery were estimated to be up to 95% higher than the net profit obtained in the chitosan production process from shrimp exoskeleton [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…. Ex out (13) The exergy efficiency of the process and the contribution of each stage to exergy loss were defined by Equations ( 14) and ( 15), respectively.…”
Section: Ex In −mentioning
confidence: 99%
“…The sustainability of biorefinery systems is assessed via methodologies such as techno-economic assessment, exergy analysis, life-cycle assessment, a waste reduction algorithm and inherent safety [12,13]. The exergy approach has been widely used to analyze and improve processes since it enables the identification of energy degradation by measuring losses and irreversibilities [14].…”
Section: Introductionmentioning
confidence: 99%
“…5 Then, under this concept, it is possible to obtain environmentally friendly fuels, take advantage of residues to manufacture by-products with a high added value, in turn generate economic and energy stability, and reduce negative effects on the environment and health; in other words, biorefinery implementation for biomass valorization provides several benefits due to the diversification of raw materials and products while dealing with sustainability issues. 6,7 In this study, a methodology for biorefinery synthesis was developed, considering technical, economic, and exergetic factors, to determine the convenience of additional investments. The methodology was applied to a biorefinery based on African palm as a case study, biomass found in 124 municipalities in Colombia, 8 and was gaining great importance in different industries.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the biorefinery concept incorporates a wide range of technologies capable of separating biomass into its basic components and converting them by integrating processes and equipment for conversion into value-added products, biofuels, and chemicals . Then, under this concept, it is possible to obtain environmentally friendly fuels, take advantage of residues to manufacture by-products with a high added value, in turn generate economic and energy stability, and reduce negative effects on the environment and health; in other words, biorefinery implementation for biomass valorization provides several benefits due to the diversification of raw materials and products while dealing with sustainability issues. , …”
Section: Introductionmentioning
confidence: 99%